Microalgal lutein biosynthesis: Recent trends and challenges to enhance the lutein content in microalgal cell factories - Patel, Alok; Rova, Ulrika; Christakopoulos, Paul; Matsakas, Leonidas (Frontiers in Marine Science, 2022)
Photosynthetic organisms such as eukaryotic microalgae and prokaryotic cyanobacteria synthesize a wide range of valuable chemicals. They are predicted to become efficient and renewable sources for valuable products in the future due to their high biomass synthesis using CO2 and solar energy. Microalgae are producers of several carotenoids including lutein, which is a xanthophyll carotenoid with several health advantages, including the prevention of age-related macular degeneration. Currently, it is extracted on commercial scale from marigold flower petals, however, production from plant sources is highly affected by seasonal variations, requires arable land, and has high production cost. Microalgae, on the other hand, are an ideal alternative for lutein synthesis due to their rapid growth and high biomass and lutein yield. It is, however, necessary to further improve lutein productivity, for a successful transition to commercial production. This article describes lutein biosynthesis in microalgae by using their native biochemical pathways, as well as possible target genes for genetic engineering to enhance lutein production. Understanding the processes behind lipid droplet synthesis in chloroplasts, as well as carotenoid transport across chloroplast membranes and carotenoid esterification, might lead to novel ways to boost lutein levels in microalgae.